Natural features of Rudnik mountain as development factors of sustainable tourism types - Milica Cvetanović (Mенаџмент у хотелијерству и туризму, 2015)
Rudnik is the most attractive mountain in Šumadija Mountains Range. The main reason is the large number of peaks, six of which exceed 1000 m above sea level. Its natural resources, especially floral, geomorphological and climatological, make Rudnik an oasis for relaxation and recreation. This is supported by the fact that as far back as in 1922 it was proclaimed an air spa. The development of sustainable types of tourism on Rudnik would also contribute to the economic growth of the local community. Despite its excellent geographic position and transport connections, tourism on Rudnik is not developed sufficiently. The aim of this paper is to present, through both field and literary research of Rudnik, all the natural elements of this mountain and the way they can influence the future development of sustainable types of tourism.